Economic uncertainty, monetary uncertainty and money demand in Pakistan: An asymmetrical analysis - Mukhtar, Tahir; Adnan, Saira; Jehan, Zainab (Economic Journal of Emerging Markets, 2026)
Purpose — Adopting an asymmetric approach, this study analyses the impact of economic and monetary uncertainties on money demand within an open-economy framework for Pakistan. Its primary objective is to assess whether the positive and negative components of each type of uncertainty deliver a differential impact on money demand. Methods — The study employs the Nonlinear Autoregressive Distributed Lag (NARDL) framework to examine the long-run and short-run money demand function over the period 1975–2024.Findings — The results reveal distinct asymmetric effects. Rising economic uncertainty (VY) decreases money demand, while a decline in economic uncertainty has a positive but comparatively weaker effect. Conversely, increasing monetary uncertainty (VM) drives up demand, while a decline in monetary uncertainty reduces money demand. These findings suggest that for the positive component of VY, the substitution effect dominates the precautionary effect; however, as VM increases, the precautionary effect overwhelms the substitution effect. The overall findings also indicate that agents are more sensitive to real sector volatility than to monetary volatility. Moreover, the exchange rate, along with traditional determinants, significantly influences short- and long-run money demand. Implication — The results suggest that monetary authorities should consider the source and sign of uncertainty shocks to properly anticipate liquidity needs and achieve monetary stability. Originality — This study is the first of its kind in Pakistan to explore the asymmetric relationship among economic volatility, monetary volatility, and money demand within an open-economy framework